Effect of surfactant mediated inter-particle interactions on the magnetic properties of Manganese Zinc Ferrite ferrofluid. Issue 1 (July 2021) - ReenaMary, A. P.; Divya, D.; Jestin, M. G.; Omari, Imad Al; Anantharaman, M R
Abstract: Ferrofluids of spinel ferrites presents a multitude of applications in engineering and biomedical fields. The nature of the divalent ions and their occupancy decides the magnetic properties of the spinel ferrites. The nanoparticles of these ferrites and their suspensions in various liquids are of great fundamental interest as well. This paper reports the synthesis and magnetic relaxation studies on fluid particles of Zinc substituted manganese ferrite. Nanoparticles of manganese zinc ferrite with a particle size around 5 -6 nm, are synthesized by chemical method and suspended in kerosene and water, with proper surfactants. The structural characterization is carried out by x-ray diffraction and electron microscopy. The magnetic properties are studied by employing a SQUID magnetometer. The temperature dependent static magnetic measurements and analysis reveal the inter particle interaction effects on the overall magnetic behavior of the constituent magnetic nanoparticles. The modification of the magnetic relaxation based on the surfactant is analysed.